Use of Distributed Electricity Generation Technologies in Hotels - Vourdoubas, John (International Journal of Global Sustainability, 2021)
Distributed electricity generation technologies have increasing applications worldwide in various sectors due to their environmental and economic benefits. In the present study the use of these technologies in hotel industry is investigated. Various distributed electricity technologies, including co-generation of heat and power systems, are examined. Some of them are using renewable energies like solar energy, wind energy and biomass for electricity generation. Others are related with various co-generation systems including fuel cells. Many hotels require almost equal amounts of heat and electricity in their daily operations. Co-generation technologies have the advantage that they can cover almost all of their requirements in both electricity and heat. Some distributed electricity generation technologies including solar photovoltaic energy, co-generation systems, wind turbines and fuel cells are already used in hotels. Their energy efficiency varies in the range of 10% to 90%. Technologies using renewable energies generate carbon-free electricity while others fueled by natural gas generate electricity with low carbon impacts. Each technology has advantages and drawbacks while the possibility of using each technology depends on hotel’s characteristics as well as on the local availability of renewable energy sources. The results of the present study are important in hotel industry since they indicate the possibility of using the environmentally friendly distributed electricity generation technologies for covering their electricity as well as, in some cases, their heating requirements reducing their carbon footprint due to energy use and increasing their energy and environmental sustainability.